Starategi Distribusi Pemasaran Pada Sepatu Compass - Muhammad Miftahul Qolbi; Ahmad Vajri Rahman (CV. ITTC INDONESIA, 2026)
The increasingly competitive fashion industry requires companies to develop effective marketing strategies, particularly in distribution management. Distribution is no longer viewed merely as a logistical function but as a strategic instrument for creating brand value and customer experience. This study aims to analyze the distribution strategy of Sepatu Compass as a local footwear brand and to understand its role in supporting marketing effectiveness and brand image. This research employs a qualitative descriptive approach using secondary data obtained from literature studies, documentation, and indirect observation of Compass’s official distribution channels. The data were analyzed through thematic classification and interpreted using relevant distribution and marketing theories. The findings indicate that Sepatu Compass implements a selective distribution strategy by combining direct-to-consumer and one-level distribution channels through official retailers and verified digital platforms. The company also applies a limited product release system to maintain exclusivity and brand control. These strategies contribute to strengthening brand image, enhancing customer loyalty, and maintaining competitive advantage in the national footwear industry. The study concludes that a controlled and integrated distribution strategy plays a crucial role in supporting the sustainability and competitiveness of local fashion brands.